2022
DOI: 10.3389/fcvm.2022.988271
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Right ventricular outflow tract obstruction caused by multicomponent mesenchymal tumor

Abstract: Right ventricular outflow tract obstruction (RVOTO) is a cause of hemodynamic instability that can lead to right ventricular dysfunction. Cardiac tumors located in the right ventricle or surrounding structures can cause RVOTO. Herein, we present a rare case of a 21-year-old male with palpitations due to RVOTO caused by a cardiac multicomponent mesenchymal tumor. The tumor was localized in the right ventricular outflow tract, resulting in right side heart enlargement, tricuspid regurgitation, and RVOTO. Hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Clinically, there may be a systolic murmur, hypovolemia, or shock. Other signs include a mediastinal mass or pericardial effusion [1,[3][4][5][6][7][8]. Its management hinges on the cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, there may be a systolic murmur, hypovolemia, or shock. Other signs include a mediastinal mass or pericardial effusion [1,[3][4][5][6][7][8]. Its management hinges on the cause.…”
Section: Discussionmentioning
confidence: 99%
“…In reviewing the literature, there are few reported cases of RVOTO. Huang et al reported a mesenchymal tumor diagnosed as an atypical capillary hemangioma, where surgical excision of the mass resulted in a favorable outcome [7]. Zeng et al described two postoperative cases where RVOTO was complicated using vasopressors, advising against their use in such scenarios [8].…”
Section: Discussionmentioning
confidence: 99%